The Continuity of Personality’s Sensory Development: Pre-School, School Education - Barbashova, Iryna (Pedagogical Discourse, 2013)
The general trends in the provision of perceptual development of children and pupils: cross-cutting nature of the implementation of the tasks of sensory development from pre-school educational institutions to high school are established; the presence of distinct ways to improve the visual, audial and tactile perception; the gradual expansion of the objects and phenomena’ external properties that are of survey; the use of targeted and indirect approaches to the formation of sensual sphere of personality.